1993
DOI: 10.1086/452068
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Income Effects of Migrant Remittances: A Methodological Approach Applied to Greece

Abstract: I. Introduction There is an ongoing debate on how the often voluminous migrant remittances are used and to what extent they contribute to the development of the migrant's country of origin. There are surveys on how remittance recipients spend their income and discussions on how effective government policies are in attracting remittances. In fact, there is quite a literature, often negative, concerning the contribution of remittances to productive investment. This literature looks at remittances in a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 6 publications
2
70
0
3
Order By: Relevance
“…Although there was a difference in the two studies regarding the main use of remittances, one factor that was common amongst them was the fact that less than 20% of remittances were used for investment purposes. A later study by Glytsos (1993) showed, in the case of Greece, very similar results to Gilani et al (1981). Oberai and Singh (1980) provided results for the Indian Punjab showing that the majority of remittances to households in this part of India were spent on food and clothing, followed by housing and household goods.…”
supporting
confidence: 75%
“…Although there was a difference in the two studies regarding the main use of remittances, one factor that was common amongst them was the fact that less than 20% of remittances were used for investment purposes. A later study by Glytsos (1993) showed, in the case of Greece, very similar results to Gilani et al (1981). Oberai and Singh (1980) provided results for the Indian Punjab showing that the majority of remittances to households in this part of India were spent on food and clothing, followed by housing and household goods.…”
supporting
confidence: 75%
“…Of particular interest is the finding that spending on consumption and investment produced similar multipliers of respectively 1.8 and 1.9. And contrary to common opinion, expenditure on housing was found to be very productive, with a multiplier of 2 (Glytsos [48]). By carrying out an econometric test on data from 11 Central and Eastern European countries, Léon-Ledesma and Piracha [68] found that remittances significantly contribute to the increase of the investment level of the source economies.…”
Section: Impact Of Remittances On Economic Growthmentioning
confidence: 78%
“…Some of the studies that find a positive relationship between remittances and different types of household investments are Taylor (1992), Glytsos (1993), Brown (1994), Adams (1998), Massey and Parrado (1998), Rozelle et al, (1999), McKormick and Wahba (2001), Muent et al, (2001), Dustmann and Kirchkamp (2002), Kule et al, (2002), Taylor et al, (2003), Zarate -Hoyos (2004), Woodruff and Zenteno (2007) and Yang (2007). Other studies argue that remittances are absorbed into immediate consumption so they don't finance productive investments.…”
Section: Previous Literaturementioning
confidence: 99%